2010
DOI: 10.1111/j.1365-2966.2009.15995.x
|View full text |Cite
|
Sign up to set email alerts
|

The cool side of Lyman alpha emitters

Abstract: We extend a previous study of Lyman alpha emitters (LAEs) based on hydrodynamical cosmological simulations, by including two physical processes important for LAEs: (i) Lyα and continuum luminosities produced by cooling of collisionally excited H i in the galaxy and (ii) dust formation and evolution; we follow these processes on a galaxy‐by‐galaxy basis. H i cooling on average contributes 16–18 per cent of the Lyα radiation produced by stars, but this value can be much higher in low‐mass LAEs and further increa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
123
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(132 citation statements)
references
References 71 publications
8
123
1
Order By: Relevance
“…We assume here that Lyα suffers the same dust extinction as LyC, a simple treatment that is unlikely to capture the complex radiative transfer physics of the Lyα line as it propagates through the dusty ISM (see, e.g., Caplan & Deharveng 1986;Neufeld 1991;Dijkstra 2009;Scarlata et al 2009;Dayal et al 2010). Inserting Equation (57) into (2) yields the additional flux observed at ν o ν α from galaxy Lyα: where 1 + z α = (ν α /ν o )(1 + z o ).…”
Section: Lyα Emission From Galaxiesmentioning
confidence: 99%
“…We assume here that Lyα suffers the same dust extinction as LyC, a simple treatment that is unlikely to capture the complex radiative transfer physics of the Lyα line as it propagates through the dusty ISM (see, e.g., Caplan & Deharveng 1986;Neufeld 1991;Dijkstra 2009;Scarlata et al 2009;Dayal et al 2010). Inserting Equation (57) into (2) yields the additional flux observed at ν o ν α from galaxy Lyα: where 1 + z α = (ν α /ν o )(1 + z o ).…”
Section: Lyα Emission From Galaxiesmentioning
confidence: 99%
“…We also self-consistently compute the dust mass and attenuation for each galaxy in the simulation box assuming type II SN (SNII) to be the main dust producers (Maiolino et al 2006;Stratta et al 2007). The dust mass is converted into an optical depth to UV photons assuming the dust is made of carbonaceous grains spatially distributed as the gas (see Dayal et al 2010 andFerrera 2012 for complete details of this calculation). The predicted observed UV luminosity is then L obs c = L int c × fc, where fc is the fraction of continuum photons that escape unattenuated by dust.…”
Section: Comparison With Galaxy-formation Model Predictionsmentioning
confidence: 99%
“…This is easily understood, as we will see later on, as a result of the relatively low stellar masses and metallicities characterizing these objects. Dust can, however, become more important in luminous Lyman break galaxies (LBGs) and Lyman alpha emitters (LAEs) as many studies have shown (Lai et al 2007; Atek et al 2008; Dayal, Ferrara & Gallerani 2008; Nagamine, Zhang & Hernquist 2008; Dayal et al 2009; Finkelstein et al 2009; Dayal, Ferrara & Saro 2010; Dayal, Maselli & Ferrara 2011).…”
Section: Luminosity Functionmentioning
confidence: 99%